Single-cell RNA sequencing reveals the effects of high-fat diet on oocyte and early embryo development in female mice - Qi Zhu; Feng Li; Hao Wang; Xia Wang; Yu Xiang; Huimin Ding; Honghui Wu; Cen Xu; Linglin Weng; Jieyu Cai; Tianyue Xu; Na Liang; et al. (BMC, 2024)
Abstract Background Obesity is a global health issue with detrimental effects on various human organs, including the reproductive system. Observational human data and several lines of animal experimental data suggest that maternal obesity impairs ovarian function and early embryo development, but the precise pathogenesis remains unclear. Methods We established a high-fat diet (HFD)-induced obese female mouse model to assess systemic metabolism, ovarian morphology, and oocyte function in mice. For the first time, this study employed single-cell RNA sequencing to explore the altered transcriptomic landscape of preimplantation embryos at different stages in HFD-induced obese mice. Differential gene expression analysis, enrichment analysis and protein-protein interactions network analysis were performed. Results HFD-induced obese female mice exhibited impaired glucolipid metabolism and insulin resistance. The ovaries of HFD mice had a reduced total follicle number, an increased proportion of atretic follicles, and irregular granulosa cell arrangement. Furthermore, the maturation rate of embryonic development by in vitro fertilization of oocytes was significantly decreased in HFD mice. Additionally, the transcriptional landscapes of preimplantation embryos at different stages in mice induced by different diets were significantly distinguished. The maternal-to-zygotic transition was also affected by the failure to remove maternal RNAs and to turn off zygotic genome expression. Conclusions HFD-induced obesity impaired ovarian morphology and oocyte function in female mice and further led to alterations in the transcriptional landscape of preimplantation embryos at different stages of HFD mice.